2023
DOI: 10.3346/jkms.2023.38.e64
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Patient Blood Management Program on the Appropriateness of Red Blood Cell Transfusion and Clinical Outcomes in Elderly Patients Undergoing Hip Fracture Surgery

Abstract: Background Elderly patients with hip fractures frequently receive perioperative transfusions, which are associated with increased morbidity and mortality. This study aimed to evaluate the impact of a patient blood management (PBM) program on the appropriateness of red blood cell (RBC) transfusion and clinical outcomes in geriatric patients undergoing hip fracture surgery. Methods In 2018, the revised PBM program was implemented at the Korea University Anam Hospital, Seo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Moreover, physicians may be less likely to initiate massive transfusion in patients who may have a decreased ejection fraction and would poorly tolerate volume. Nonetheless, massive transfusion protocols have been shown to effectively decrease mortality in elderly trauma patients, especially early in administration [ [24] , [25] , [26] , [27] ]. In addition, massive transfusion has been shown to improve coagulation function, alleviate organ dysfunction, and shorten the length of ICU stay in elderly populations [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, physicians may be less likely to initiate massive transfusion in patients who may have a decreased ejection fraction and would poorly tolerate volume. Nonetheless, massive transfusion protocols have been shown to effectively decrease mortality in elderly trauma patients, especially early in administration [ [24] , [25] , [26] , [27] ]. In addition, massive transfusion has been shown to improve coagulation function, alleviate organ dysfunction, and shorten the length of ICU stay in elderly populations [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growing data suggests that age is not an independent risk factor for increased mortality after trauma and elderly patients who otherwise meet criteria for transfusion have better outcomes when transfused aggressively [ [24] , [25] , [26] ]. The factors that contribute to increased mortality in older trauma patients are multifactorial and more data are required to further guide clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although controversial, numerous studies have indicated that the use of perioperative blood products is associated with several adverse events [ 10–15 ]. Identifying patients at high risk for perioperative transfusion early in their admission and implementing patient blood management (PBM) can significantly reduce transfusion requirements [ 16 , 17 ], offering a therapeutic opportunity to avoid transfusions and enhance patient prognosis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%